Online misinformation and cohesive societies - Yaacob Ibrahim (2022)
The Internet has enabled misinformation to spread wildly, divide people easily, and incite violence and chaos quickly. Regulatory approaches and effective actions by individuals and civil society are needed to curb misinformation and contain the harm to social cohesion.